Рухові порушення, індуковані ішемією мозку, за умов електричного подразнення палеоцеребелярної кори мозочка = Brain ischemic damage motor disturbances in conditions of paleocerebellar cortex electrical stimulations - Desyatsky, V. V.; Bylsky, D. V. (Journal of Education, Health and Sport, 2015)
Desyatsky V. V., Bylsky D. V. Рухові порушення, індуковані ішемією мозку, за умов електричного подразнення палеоцеребелярної кори мозочка = Brain ischemic damage motor disturbances in conditions of paleocerebellar cortex electrical stimulations. Journal of Education, Health and Sport. 2015;5(9):613-620. ISSN 2391-8306. DOI10.5281/zenodo.31727 http://dx.doi.org/10.5281/zenodo.31727 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A613-620 https://pbn.nauka.gov.pl/works/640884 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. УДК: 612.826+612.8.-009 руховІ порушенНЯ, ІНДУКОВАНІ ІШЕМІЄю мозку, за умов електричного подразнення палеоцеребелярної кори мозочка brain ischemic damage MOTOR disturbances IN conditions of paleocerebellar cortex electrical stimulations В. В. Десятський. Д. В. Бильський V. V. Desyatsky, D. V. Bylsky Одеський національний медичний університет, Одеса Odessa National Medical University, Odessa Summary In Wistar rats the bilateral ligation of common arterii carotici served as a model of hypoxic damage of brain. It was established that ES (100 Hz) of paleocerebellar cortex (nodulus, uvula) was followed by the reduction of the lethality of animals, increasing of the period of preserved pain susceptibility along with the ability to maintain the vertical posture and static reflexes. Low- frequency ES (10 Hz) was less effective with regard to retardation of hypoxic- induced locomotor disturbances. Keywords: motor activity, paleocerebellar cortex, electrical stimulation, brain ischemic damage. Резюме У щурів лінії Вістар білатеральною перев’язкою загальних сонних артерій викликали гіпоксичне ушкодження мозку. ЕП (100 Гц) палеоцеребелярних відділів (nodulus, uvula) супроводжувалось зменшенням летальності тварин, збільшенням періоду збереження больової чутливості, утримування в вертикальному положенні і збереження статичних рефлексів. Менш ефективною було низькочастотне ЕП (10 Гц) палеоцеребелярної кори. Ключові слова: рухова активність, палеоцеребелярна кора, електричне подразнення, ішемічне ураження мозку. Резюме ДВИГАТЕЛЬНЫЕ НАРУШЕНИЯ, ВЫЗВАННЫЕ ИШЕМИЕЙ МОЗГА, В УСЛОВИЯХ ЭЛЕКТРИЧЕСКОЙ СТИМУЛЯЦИИ ПАЛЕОЦЕРЕБЕЛЛЯРНОЙ КОРЫ МОЗЖЕЧКА. У крыс линии Вистар билатеральной перевязкой общих сонных артерий вызывали гипоксическое поражение мозга. ЭС (100 Гц) палеоцеребеллярных отделов коры (nodulus, uvula) сопровождалась уменьшением летальности животных, увеличением периода сохранения болевой чувствительности, удерживания вертикального положения и сохранения статических рефлексов. Менее эффективной была низкочастотная ЭС (10 Гц) палеоцеребеллярной коры. Ключевые слова: двигательная активность, палеоцеребеллярная кора, электрическая стимуляция, ишемическое повреждение мозга.